2021
DOI: 10.3389/fmars.2021.756076
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Atmospheric Input of Seawater-Dissolvable Pb Based on the Budget of 210Pb in the East Sea (Japan Sea)

Abstract: In order to determine the atmospheric input of 210Pb and seawater-dissolvable Pb in the East Sea (Japan Sea), we measured the concentrations of total 210Pb and dissolved Pb (<0.2 μm) in seawater and 210Pb and 226Ra in sinking particles. The East Sea is deep (∼3700 m) and enclosed by surrounding continents except for the shallow sills (<150 m). Since the East Sea is located off the East Asian continent under the westerlies, the concentrations of 210Pb and dissolved Pb in this sea are significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…By assuming the steady state of eq , the scavenging rate constant ( k ) is calculated to be 0.02 yr –1 , corresponding to the 50 years of dissolved Fe residence time in this sea. The calculated value approaches the lower limit of that in the North Pacific Ocean (30–140 years), , likely due to the effective scavenging of particle-reactive elements in the East Sea. , The result of eq is striking because approximately 25% of the dissolved Fe in this sea is anthropogenic (Figures and S5c). This rapid Fe evolution in the ocean is considered to be due to the 9-fold increase in atmospheric deposition of anthropogenic Fe in East Asia over the past 50 years (1965–2017) relative to the short residence time of Fe in seawater (∼50 years).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…By assuming the steady state of eq , the scavenging rate constant ( k ) is calculated to be 0.02 yr –1 , corresponding to the 50 years of dissolved Fe residence time in this sea. The calculated value approaches the lower limit of that in the North Pacific Ocean (30–140 years), , likely due to the effective scavenging of particle-reactive elements in the East Sea. , The result of eq is striking because approximately 25% of the dissolved Fe in this sea is anthropogenic (Figures and S5c). This rapid Fe evolution in the ocean is considered to be due to the 9-fold increase in atmospheric deposition of anthropogenic Fe in East Asia over the past 50 years (1965–2017) relative to the short residence time of Fe in seawater (∼50 years).…”
Section: Resultsmentioning
confidence: 67%
“…The atmospheric depositional flux of water-soluble Fe (sFe natural + sFe anthro ) to the marginal sea (East Sea) can be measured using 210 Pb as a tracer from the following equation: Atm normalsFeanthro or sFenatural = Atm Pb 210 × false( sFe anthro normalor sFe natural / 210 Pb false) aerosol where Atm sFeanthro or sFenatural and Atm Pb‑210 represent the atmospheric deposition of sFe anthro or sFe natural (mg m –2 yr –1 ) and 210 Pb (dpm m –2 yr –1 ), respectively. In this sea, the atmospheric depositional flux of 210 Pb was accurately obtained from the oceanic mass balance model of Seo et al The uncertainties for eq were determined by considering the uncertainties from the atmospheric input of 210 Pb, the uncertainties from the calculated anthropogenic and natural Fe in water-soluble fraction, and the counting errors of 210 Pb in aerosols. For calculating Atm sFenatural , we used the integrated ratio of sFe natural to excess 210 Pb in each sample.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 210 Pb can be used to understand the observed behavior of Pb in the ocean. 210 Pb has been studied to trace the behavior of anthropogenic Pb in the marine environment using ratios of Pb/ 210 Pb [10][11][12][13][14]. Recently, seawater-dissolvable Pb was quantified using the scavenging rate of 210 Pb [14].…”
Section: Introductionmentioning
confidence: 99%
“…210 Pb has been studied to trace the behavior of anthropogenic Pb in the marine environment using ratios of Pb/ 210 Pb [10][11][12][13][14]. Recently, seawater-dissolvable Pb was quantified using the scavenging rate of 210 Pb [14]. Despite these various studies, Pb is known to have a wide range of solubility in seawater (13-90%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring particle‐reactive radionuclides, with long‐lived parent and short‐lived daughter, such as 210 Po (half‐life, T 1/2 : 138.4 days): 210 Pb ( T 1/2 : 22.3 years), 210 Pb: 226 Ra ( T 1/2 : 1,600 years) have been widely utilized as tracers in shelf, slope and deep ocean to quantify oceanic processes, including: (a) estimate export fluxes of particulate organic carbon, biogenic silica, carbonate, key trace metals, and other contaminants (e.g., Anand et al., 2018; Anderson, 2020; Bam et al., 2021; Buesseler et al., 1992; Cochran & Masque, 2003; Friedrich & Rutgers van der Loeff, 2002; Gustafsson et al., 1997; Hayes et al., 2018; Rutgers van der Loeff & Geibert, 2008; Seo et al., 2021; Shimmield et al., 1995); (b) quantify particle dynamics such as aggregation/disaggregation (Murnane et al., 1994; Nozaki & Tsunogai, 1976; Rigaud et al., 2015); (c) vertical and lateral transport of particles and particle‐reactive chemical species (e.g., Anand et al., 2018; Chen et al., 2012; Gustafsson et al., 1997; He et al., 2015; Hu et al., 2014; Lepore et al., 2009; Smith et al., 2003); (d) scavenging rate/residence time of these nuclides in the dissolved, particulate and total phases (e.g., Bacon & Anderson, 1982; Bacon et al., 1976; Niedermiller & Baskaran, 2019; Rigaud et al., 2015); (e) settling velocity of particles (e.g., Krishnaswami et al., 1976; Moore & Smith, 1986; Somayajulu & Craig, 1976); (f) vertical variations in the extent of remineralization of sinking biogenic particulate matter (e.g., Niedermiller & Baskaran, 2019); and (g) tracer for quantifying biogeochemical cycling of other particle‐reactive species such as stable Pb (Schaule & Patterson, 1981; Sherrell & Boyle, 1992). Earlier studies from global oceans have shown disequilibrium between 210 Pb and 226 Ra in most of the deep oceanic water column and using 210 Pb/ 226 Ra activity ratio (AR), residence times of 210 Pb in deep waters of the open ocean were reported to vary from 18 to > 300 years (Cochran, 1992; Cochran et al., 1983; Craig et al., 1973; Niedermiller & Baskaran, 2019; Nozaki et al., 1976; Rigaud et al., 2...…”
Section: Introductionmentioning
confidence: 99%